Measuring adverse childhood experiences by interviewing children at 9 and 10 years of age : Prevalence, concordance with mother-reports, posttraumatic stress disorder symptoms, and subjective experience of being asked about adverse childhood experiences in FinnBrain Birth cohort study - Kataja, Eeva-Leena; Tuulari, Jetro J.; Karlsson, Linnea; Sinisalo, Susanne; Autere, Tuomo-Artturi; Perasto, Laura; Juusola, Aino; Salama, Essi; Aatsinki, Anna-Katariina; Karlsson, Hasse (ELSEVIER SCIENCE INC, 2025)
How children experience the screening of adverse childhood experiences (ACEs) is little studied. Moreover, the similarity between parental and child reports is unknown. We interviewed 9-yearolds (a subsample of the FinnBrain Birth Cohort Study; N = 344) by using the Pediatric ACEs and Related Life Events Screener questionnaire (PEARLS; covering 10 traditional ACEs and 7 expanded items). Furthermore, we asked about the subjective harm caused by ACEs, posttraumatic stress disorder (PTSD) symptoms, and how the children experienced the interview. The mothers (N = 348) filled out the PEARLS youth questionnaire that provided a parental report on ACEs. In total, 39.2% of children self-reported zero ACEs, and the corresponding percentage for mother-reports was 30.2%. In addition, 7.8% of children reported having been exposed to >= 4 (of 17 possible) ACEs, which is an often-used cutoff score for adverse health outcomes. The corresponding percentage for mother-reports was higher at 14.7%. There was low concordance between mother-and child reports in cases where ACEs did happen 4.9% of children with at least 1 ACE reported PTSD symptoms. In gen-eral, 1.7% of children felt that it was difficult to answer the ques-tions, whereas 78.6% felt that it was easy. Negative feelings (e.g., anxiety, depression) related to the interview were reported by 0.9% to 1.4% of the children. In addition, 2% reported only negative feelings, whereas 80% reported only positive feelings. The preva-lence of ACEs at 9 and 10 years of age in the FinnBrain Birth Cohort was comparable to that in many retrospective adult studies in European general populations. The prevalence of PTSD symp-toms was low and was not clearly linked to the number of self reported ACEs. The observation that most children found the inter-view to be easy, neutral, or positive is encouraging, whereas the uneasiness of few children at the interview needs to be acknowledged.